Calendar Online Technology Development to Support Asset Lending Digitalization - Amin Fauzi, Andy Kristanto, Syunu Trihantoyo (Lembaga Bale Literasi, 2025)
The advancement of digital technology has prompted higher education institutions to enhance the efficiency of their administrative services, which includes managing facility and infrastructure loans. Issues like overlapping schedules, limited information access, and ineffective manual management frequently affect the quality of service. This research aimed to investigate how calendar. Online can enhance the efficiency of the facility and infrastructure loan system at the Faculty of Social Sciences and Law, Universitas Negeri Surabaya. A qualitative approach was taken for this study, utilizing literature reviews and system implementation analysis as main methods. Data collection involved scientific literature, institutional documents, and observations on how the system was implemented. The findings revealed that the use of calendar. Online boosted administrative efficiency by 78%, diminished scheduling conflicts by 65%, and enhanced user access as well as transparency regarding borrowing information. Additionally, around 85% of users reported that the system was more user-friendly and practical than the previous manual approach. These results suggest that digital scheduling systems have a beneficial impact on administrative effectiveness within higher education institutions. In summary, the introduction of calendar. Online has meaningfully improved the efficiency, clarity, and performance of facility borrowing services. Future enhancements are suggested through the integration with notification systems and institutional databases to further elevate service quality.